Investigation of microgrid instability caused by time delay - Aghanoori, N.; Masoum, Mohammad Sherkat; Islam, Syed; Nethery, S. (IEEE, 2018)
© 2017 EMO (Turkish Chamber of Electrical Enginners). This paper investigates the impact of time delay in the control of a grid-connected microgrid with renewable energy resources. The considered microgrid has a critical load that needs to be powered and protected in the event of grid voltage disturbance while the microgrid maintains connection to the grid. Three case studies are performed considering three different time delays to indicate the advantages of fast communication system in the performance of renewable microgrids. Detailed simulation results illustrate that the proposed communication system using IEC 61850 substation automation standard provides better voltage and current quality to the critical local load with larger phase and gain margins while keeping the microgid connected to main grid.